Spanish Identity: Nation, Myth, and History - Jesús Torrecilla (Studies in 20th & 21st Century Literature, 2009)
In the last two centuries, conservatives and liberals have offered two mutually exclusive visions of Spanish history, each with distinct myths, symbols, and heroes. The conservative image, formed in the Middle Ages, was based on the myth of the Reconquest and the need to restore (or keep) the homogeneity of a country characterized by its Christian religion and Latin culture. At the beginning of the nineteenth century, faced with Napoleon’s invasion, Spanish liberals understood the danger of associating their modern ideas with France and invented a progressive and democratic Spanish tradition. According to their interpretation, the most authentic Spain was not the one identified with the Reconquest and the Empire, but the Spain of all those who had been excluded from the nation-building process because of their religion or ideas: the tolerant al-Andalus Muslims, the freedom-fighter comuneros and the defenders of the democratic medieval fueros. The great success of the transition to democracy and the Constitution of 1978 resided in the ability of all different tendencies and parties to overcome this division, to build bridges and create a common national project. For the first time in history, Spaniards managed to build a successful society based on consensus, pluralism and democracy. However, as a reality based on agreements, its nature is fragile. What is at stake now in Spain is to strengthen the viability of this model.
Keywords: Spanish history; heterotopia; Reconquest; Christianity; Latin culture; progressive; comuneros; fueros; al-Andalus; national identity